PENYIDIKAN TERHADAP KEPALA DESA YANG DENGAN SENGAJA MELAKUKAN TINDAKAN YANG MENGUNTUNGKAN SALAH SATU PASANGAN CALON PADA SENTRA PENEGAKAN HUKUM TERPADU (Studi Pada Satuan Reserse Kriminal Kepolisian Resor Pariaman) - Alva Zakya Akbar (UNES Law Review, 2020)
canditates are criminal acts regulated in Article 71 paragraph (1) and Article 188 of Law Number 10 Year 2016 concerning the Election of Governors, Regents and Mayors. In the election of Mayor Pariaman in 2018 there was a criminal offense due to the election of the state officials, namely the Village Head who during the face-to-face campaign between the community and the candidate pair gave remarks containing the invitation to choose the candidate pair. As a result of these actions, the Village Head was reported to the Gakkumdu Center for the Pariaman City Election Supervisory Committe and subsequently forwarded to the Pariaman Police Secretariat with Number: LP / B / 57 / III / 2018 / SPKT / Polres on March 29, 2018 for an investigation.